Defect-induced nucleation and epitaxial growth of a MOF-derived hierarchical Mo2C@Co architecture for an efficient hydrogen evolution reaction. Issue 23 (6th April 2020) - Zhang, Linfei; Zhu, Jingting; Shi, Yumeng; Wang, Zhuo; Zhang, Wenjing
Abstract : In this work, we report a new strategy to synthesize efficient 3D hierarchical catalysts composed by Mo2 C nanosheets and Co nanoparticles (H-Mo2 C@Co). The Mo2 C and Co makes a synergistic effect in improving HER via providing large surface areas. Abstract : The 3D hierarchical structure in catalysts not only the preserves intrinsic characteristics of each component, but also achieves increased specific surface area and active sites for the hydrogen evolution reaction (HER). Herein, we report a new strategy to synthesize efficient 3D hierarchical catalysts composed of Mo2 C nanosheets and Co nanoparticles (H-Mo2 C@Co). It was realized by using raw materials, defect-rich MoO x, Co(NO3 )2 ·6H2 O and 2-methylimidazole, to design Mo/Co bimetallic metal–organic frameworks (BMOFs), followed by pyrolysis at 800 °C. The defects in MoO x induced preferential nucleation and growth of the BMOFs so that they can ensure the construction of a stable 3D hierarchical structure. Mo2 C and Co have a synergistic effect in improving the HER via providing large surface areas (351.5 m 2 g −1 ), more active sites and optimizing charge transfer. It can achieve 10 mA cm −2 at low overpotential over a wide pH range (144 mV in 0.5 M H2 SO4 and 103 mV in 1.0 M KOH) and the properties can be well maintained in both acid and alkaline electrolyte after 2000 cycles. The hierarchical catalyst contains no noble metal, can be synthesized on a large scale and recycled by magnetic stirring, demonstrating great potential in water splitting, wastewater treatment, dye adsorption and other fields.